Insights into the porous structure of surfactant-promoted gas hydrate. (2nd February 2022) - Venet, Saphir; Guerton, Fabrice; Desmedt, Arnaud; Broseta, Daniel
Highlights: Surfactant-promoted methane hydrate grows as a porous medium. The hydrate forms the skeleton of this porous medium, which is imbibed with water. Porosity is related to the swelling of the porous hydrate (mm scale). Pore sizes are related to the imbibition rate of water in the porous hydrate (mm scale). Direct observation by microRaman spectroscopy mapping (μm scale) provide similar values. Abstract: We show how insights into the porous structure of surfactant-promoted gas hydrate can be obtained from two types of experiments that probe very different length scales. On the one hand, the observation of an existing porous hydrate being imbibed with the aqueous surfactant solution gives information as to the porosity – inferred from the volume increase – and the average pore size – inferred from the imbibition rate. On the other hand, direct pore visualization and determination of the fluid and hydrate contents at the micron scale are obtained by optical microscopy and Raman microspectroscopy. We observe a porosity in the range of 60–70% and pore sizes of about 20–30 μm for a porous methane hydrate formed from a 500 ppmw SDS (sodium dodecyl sulfate) solution under moderate subcooling.